Recurrence rates of oral leukoplakia : a retrospective study on a portuguese study population - Antunes, Mafalda Baptista Dias (My University, 2024)
Objective: To evaluate the recurrence rate of oral leukoplakia over time and the associated risk factors, including epidemiological, clinical and histopathological characteristics, in patients from an Oral Medicine and Surgery clinic in Portugal. Materials and methods: A retrospective analysis of clinical records of oral leukoplakia since 1992 was carried out. Data was extracted on gender, age, lesion location, clinical and histopathological diagnosis, degree of dysplasia, treatment and risk factors such as tobacco consumption and systemic pathologies. Exclusion criteria included insufficient records, inconclusive diagnoses or white lesions not diagnosed as leukoplakia. The data was analysed between October and December 2023. Results: The recurrence rate was 36.4 %, with most cases present with a single or double recurrence, while multiple recurrences were relatively uncommon. Malignant transformation occurred in 3.0 per cent of cases. The average age of the patients was 59.11 years. Age was identified as a weak risk factor for multiple recurrences, with an associated increase of about 6.5% and respiratory diseases increase the risk multiple recurrences of oral leukoplakia in 12.7 times when present. Immunological pathologies showed an increased the risk of recurrence by 9.35 times. Compared to smokers, non-smokers showed an average increase in the risk of recurrence of around 16.6 times. Conclusion: The recurrence of oral leukoplakia was observed in 36.4% of patients, with the majority presenting one or two recurrences. Respiratory diseases were identified as a significant risk factor for multiple recurrences, with an estimated odds ratio of 12.7. Other factors, including immunological diseases and smoking habits, were also found to influence the risk of recurrence. The study highlights the importance of close monitoring and underscores the need for further research to enhance understanding of the risk factors and recurrence of OL.

Objetivo: Avaliar a taxa de recorrência de leucoplasia oral e os fatores de risco associados, incluindo características epidemiológicas, clínicas e histopatológicas, em pacientes de uma clínica de Medicina e Cirurgia Oral em Portugal. Materiais e métodos: Foi realizada uma análise retrospetiva de registos clínicos de leucoplasia oral desde 1992. Foram recolhidos dados sobre sexo, idade, localização da lesão, diagnóstico clínico e histopatológico, grau de displasia, tratamento e fatores de risco como consumo de tabaco e patologias sistémicas. Critérios de exclusão incluíram registos insuficientes, diagnósticos inconclusivos ou lesões brancas não diagnosticadas como leucoplasia. Os dados foram analisados entre outubro e dezembro de 2023. Resultados: A taxa de recorrência foi de 36,4%, com a maioria dos casos apresentando uma ou duas recorrências; múltiplas recorrências foram menos comuns. A transformação maligna ocorreu em 3,0% dos casos. A idade média dos pacientes foi de 59,11 anos. A idade mostrou-se um fator de risco fraco, com aumento de 6,5% para recorrências múltiplas. As doenças respiratórias aumentaram o risco de recorrências múltiplas em 12,7 vezes. Patologias imunológicas mostraram um aumento do risco de recorrência em 9,35 vezes. Não fumadores apresentaram um risco de recidiva 16,6 vezes maior que os fumadores. Conclusão: A recorrência de leucoplasia oral ocorreu em 36,4% dos pacientes, com a maioria tendo uma ou duas recorrências. Doenças respiratórias foram um fator de risco significativo para múltiplas recorrências, enquanto doenças imunológicas e o tabagismo também influenciaram o risco de recorrência da lesão . Contudo, o tabagismo não foi um fator determinante neste grupo. O estudo destaca a necessidade de monitorização cuidadosa e mais pesquisas para entender melhor os fatores de risco e recorrência da leucoplasia oral.
Dissertação para obtenção do grau de Mestre no Instituto Universitário Egas Moniz
Keywords: Oral leukoplakia; Recurrence; Retrospective study; Oral pathology